The role of social capital in the sustainability of community-based waste management: a literature review from a capitalistic management perspective - Fikri Aswan; Gusriati Gusriati; Yovhandra Ockta (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to examine the role of social capital in the sustainability of community-based waste management through Waste Banks using a capitalistic management perspective as an analytical framework. The study used a systematic literature review method by analyzing 47 references from Google Scholar, Scopus, DOAJ, and accredited national journals published in the 2015–2025 period. The results of the study indicate that the main dimensions of social capital, namely trust, norms of reciprocity, and collaborative networks, have an important contribution in maintaining community participation, strengthening institutional stability, and expanding access to external resources. From a capitalistic management perspective, social capital is understood as a productive asset with strategic value because it can increase institutional efficiency, reduce transaction costs, and create sustainable competitive advantages. In addition, social capital also functions as a corrective mechanism against market failures in waste management as a negative externality. This study provides a theoretical contribution by connecting social capital theory, institutional economics, and the Resource-Based View in the context of community-based organizations.